Розробка методу та моделі верифікації знань в онтологічних системах - Климова, М. В. (Eastern-European Journal of Enterprise Technologies, 2009)
Extension of the ontological model by the verification component for accumulation and processing of the information about knowledge hybrid inference in distributed intelligent information systems is considered. A method for knowledge verification is proposed